2013
DOI: 10.3177/jnsv.59.73
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Lipid Deposition in the Liver of Rats Fed a Diet Supplemented with Branched-Chain Amino Acids under Vitamin B6 Deficiency

Abstract: 73Branched-chain amino acids (BCAAs) composed of valine, leucine, and isoleucine are essential amino acids and account for about 40% of dietary essential amino acids in body protein and about 15% of total amino acids in muscle proteins (1). BCAAs play a role in delayed onset of muscle soreness and fatigue, and suppression of fatigue in the central nervous system (2, 3). BCAAs have been also used for the prevention of hepatic encephalopathy in patients with liver cirrhosis (4, 5). Recently, sport enthusiasts ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It was reported that B 6 deficiency induced fat deposition in the livers of rats fed with 70% casein diet or 4.75% branched-chain amino acidsupplemented diet. 1,2) Similarly, in our previous studies, rats fed a B 6 -deficient diet supplemented with L-Met (0.9%) developed severe hyperhomocysteinemia accompanied by lipid deposition in the liver. 3,4) We speculated that the accumulation of liver lipids was due to decreased secretion of very low-density lipoprotein (VLDL) from the liver.…”
supporting
confidence: 62%
“…It was reported that B 6 deficiency induced fat deposition in the livers of rats fed with 70% casein diet or 4.75% branched-chain amino acidsupplemented diet. 1,2) Similarly, in our previous studies, rats fed a B 6 -deficient diet supplemented with L-Met (0.9%) developed severe hyperhomocysteinemia accompanied by lipid deposition in the liver. 3,4) We speculated that the accumulation of liver lipids was due to decreased secretion of very low-density lipoprotein (VLDL) from the liver.…”
supporting
confidence: 62%
“…4,28,29) In addition, serum PC concentration was significantly lower in B 6 -deficient rats than in pair-fed controls. 29) In an analogous fashion, Kaimoto et al 30) reported that about 50% of rats fed a diet supplemented with branched-chain amino acids during B 6 deficiency showed lipid deposition in the liver and tended to have decreased serum TG levels. Moreover, they found that rats with liver lipid deposition also had decreased TG and TC levels in VLDL.…”
Section: Discussionmentioning
confidence: 96%
“…An increased TG synthesis capacity in liver with a concomitant reduction of hepatic VLDL-related TG secretion could help to explain the higher hepatic TG content observed in animals fed with HP diet. It has been previously reported that rats supplemented with branched-chain amino acids under vitamin B6 deficiency showed TG deposition in liver partly explained by impaired secretion of VLDL [44]; this could be relevant as casein, our dietary protein source, is rich in branched-chain amino acids. Intriguingly, other authors have reported reduced liver fat accumulation in rodents with long term increase of the protein content of the diet [45][46][47][48].…”
Section: Accepted M Manuscriptmentioning
confidence: 95%